2020
DOI: 10.1002/pds.5064
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medications among elderly patients in community healthcare institutions in Beijing, China

Abstract: PurposeTo evaluate potentially inappropriate medications (PIMs) prevalence and predictors in community healthcare institutions (CHIs) for the elderly.MethodsWe conducted a retrospective observational study, deriving data of patients aged ≥60 from 66 CHIs in Beijing, 2014‐2018. The system of Criteria of PIM for Older Adults in China was applied to identify PIMs. The primary outcome was the prevalence of visits with at least one PIM; secondary outcomes were the frequency and rate per thousand visits of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…It has also been reported that 14.1% of elderly patients visiting community healthcare institutions in Beijing were taking at least one PIM (19). In our study, the prevalence of PIMs was 37.07% in the three communities studied based on the Chinese criteria, which was between the other Chinese studies listed above.…”
Section: Discussionsupporting
confidence: 61%
“…It has also been reported that 14.1% of elderly patients visiting community healthcare institutions in Beijing were taking at least one PIM (19). In our study, the prevalence of PIMs was 37.07% in the three communities studied based on the Chinese criteria, which was between the other Chinese studies listed above.…”
Section: Discussionsupporting
confidence: 61%
“…24 articles were excluded as they did not report the PIMs or polypharmacy, meeting abstracts, and the population was not elderly. Finally, 8 studies ( Fu et al, 2020 ; Huang et al, 2020 ; Ma et al, 2020 ; Zheng et al, 2020 ; Tian et al, 2021a ; He et al, 2021 ; Li et al, 2021 ; Zhao et al, 2021 ) were included in the study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study, evaluating the PIMs utilisation in the community healthcare institutions in Beijing, showed a prevalence of 16.9% in 2018. 22 Early detection of PIMs is of central importance to prevent adverse outcomes and improve geriatric care in elderly patients. 23 Interventions, including medication review, 24 pharmaceutical interventions, 20 computerised alerts, 20 25 educational training, 26 have been effective measures to improve appropriate drug use in many countries and some also resulted in clinically significant improvements.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Based on our previous study, the current PIMs prevalence in Dongcheng CHSs is ~20% 22 and this is, therefore, assumed for the control arm. Based on a conservative estimate from our review, we expect our intervention to lead to at least an 8% relative reduction in the PIMs prevalence within CHSs.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation